Evaluation of carotid intima media thickness in children with idiopathic nephrotic syndrome - Ashraf Sayed Kamel; Mohamed Mohamed Ezzat AlGhawass; Muhammad Adel Sayed; Sara Aly Roby (BMC, 2022)
Abstract Background Nephrotic syndrome is the one of the commonest renal disorders in children. Children with nephrotic syndrome (NS) are at a high risk of atherosclerosis due to hyperlipidemia, hypertension. Carotid intima media thickness (CIMT) is a surrogate marker for atherosclerosis. This study aimed to evaluate the carotid intima media thickness in children with nephrotic syndrome and its relation to different risk factors. Methods This is an observational case control study that included forty children with nephrotic syndrome and thirty healthy children as controls. The inclusion criteria were: age of 2 years or more with disease duration of minimum of 1 year and glomerular filtration rate > 90 mL/min/1.73m2. CIMT was assessed by ultrasound. Lipid profile, protein/creatinine ratio in urine and kidney function tests were done. Results The mean CIMT (mm) was significantly higher in patients with NS (0.477 ± 0.04) compared to controls (0.39 ± 0.03) (P < 0.001) even when compared across different age groups. 60% of patients had received non-steroid immunosuppressive therapy. CIMT was significantly higher in patients receiving non-steroid immunosuppressive therapy than those receiving steroids alone. Subsequently, CIMT had significant positive correlation to duration of the disease (p = 0.05), body mass index (BMI) (p = 0.03), number of relapses (p = 0.01) and diastolic blood pressures (p = 0.003). Conclusion Children with NS had significantly higher CIMT than control group. CIMT was positively correlated to disease duration, number of relapses and BMI. It was significantly higher among patients receiving non-steroid immunosuppressive therapy than those receiving steroids alone.